1982
DOI: 10.1099/00221287-128-6-1299
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Mycobacterium farcinogenes and Mycobacterium senegalense by Immunodiffusion and Thin-layer Chromatography of Long-chain Components

Abstract: Comparative immunodiffusion studies and thin-layer chromatographic analyses of whole-organism acid methanolysates were performed on 37 strains of Mycobacterium farcinogenes, Mycobacterium senegalense and Nocardia farcinica. The latter were clearly distinguished from the mycobacteria in containing a single mycolic acid methyl ester and showing more precipitinogens with nocardial than with mycobacterial and rhodococcal reference systems. The distribution of precipitinogens showed that M. farcinogenes and M. sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…farciizogenes and M . senegalense confirms earlier work which used lipid and immunological analyses (Ridell et al, 1982). In addition, the mycobactin produced by N .…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…farciizogenes and M . senegalense confirms earlier work which used lipid and immunological analyses (Ridell et al, 1982). In addition, the mycobactin produced by N .…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 76%
“…On the basis of lipid analysis (Ridell et al, 1982), M.ji2rcinogenes and M . senegalense could not be differentiated ; each contained a-mycolates and characteristic polar mycolates, derived from epoxymycolic acids, a pattern also found in M .…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Species containing relatively long-chain mycolic acids (48 to 66 carbon atoms) and MK-9 (H2) as the predominant menaquinone type, were found to be homogeneous with respect to their 16S ribosomal RNA sequences. Beside chemotaxonomic methods, numerical taxonomic studies have been found to be very important in the taxonomy of these genera (6,7,11,20,(28)(29)(30)(31)42,45).…”
mentioning
confidence: 99%
“…Mycolic acids, which are 2-alkyl, 3-hydroxy longchain fatty acids, have particular importance in the classification of actinomycetes with a wall chemotype IV based on meso-diaminopimelic acid, arabinose and galactose (Lechevalier et al, 1971;Ridell et al, 1982;Minnikin et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence, however, that strains of these mycobacterial species have frequently been mis-identified as N . farcinica (Ridell & Goodfellow, 1983;Ridell et al, 1982Ridell et al, , 1985 and reliable methods are needed to distinguish M . farcinogenes from N .…”
Section: Introductionmentioning
confidence: 99%